2023
DOI: 10.3389/fphar.2023.1228895
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the study of anesthesia-and analgesia-related mechanisms of S-ketamine

Jian-shun Zhou,
Guan-fa Peng,
Wei-dong Liang
et al.

Abstract: Ketamine is a racemic mixture of equal amounts of R-ketamine and S-ketamine and is well known to anesthesiologists for its unique dissociative anesthetic properties. The pharmacological properties of ketamine, namely, its sympathetic excitation, mild respiratory depression, and potent analgesia, are still highly valued in its use as an anesthetic for some patients. In particular, since its advent, S-ketamine has been widely used as an anesthetic in many countries due to its increased affinity for NMDA receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 135 publications
0
0
0
Order By: Relevance
“…The N -methyl- d -aspartate (NMDA) receptor antagonist ketamine produces a state of dissociative anesthesia at high dose and pain relief and mood improvement at subanesthetic doses. Dissociative symptoms already occur at low ketamine doses, an effect that usually wanes when plasma concentrations drop but sometimes persist beyond the treatment period . We recently showed that the nitric oxide (NO) donor, sodium nitroprusside (SNP), reduced dissociative symptoms during the administration of racemic ketamine (which contains isomers R- and S-ketamine) but not during infusion of esketamine (which exclusively contains the S-isomer, S-ketamine) .…”
mentioning
confidence: 99%
“…The N -methyl- d -aspartate (NMDA) receptor antagonist ketamine produces a state of dissociative anesthesia at high dose and pain relief and mood improvement at subanesthetic doses. Dissociative symptoms already occur at low ketamine doses, an effect that usually wanes when plasma concentrations drop but sometimes persist beyond the treatment period . We recently showed that the nitric oxide (NO) donor, sodium nitroprusside (SNP), reduced dissociative symptoms during the administration of racemic ketamine (which contains isomers R- and S-ketamine) but not during infusion of esketamine (which exclusively contains the S-isomer, S-ketamine) .…”
mentioning
confidence: 99%